The creation and resolution of working hour discrepancies over the life course - Weber, Enzo; Zimmert, Franziska (Nürnberg, 2017)
"Studies on labor supply have increasingly taken account of not only the actual working hours, but also of working hour preferences as well as the discrepancy between them. However, longitudinal research on this topic remains scarce. This paper contributes to the analysis of working hour discrepancies by exploring how hours mismatch emerges and resolves with special consideration of the household context. We use a rich longitudinal data set, the German Socio-economic panel (GSOEP), for a discrete duration analysis applying a fixed effects-logit estimator. With special consideration of the household context, the findings suggest that female underemployment is strongly related to household responsibilities impeding the mismatch resolution. On the contrary, the creation of female overemployment is linked to higher qualification and job autonomy. In those positions working hour discrepancies also turn out to be persistent. Male hour constraints can be associated to job positions in a similar way. Nevertheless, the results also show that household responsibilities are less important for both male under- and overemployed."